Thirty years of Alzheimer's genetics: what's new and what's next? - Bertram, Lars (Henry Stewart Talks, 2010)
Alzheimer's Disease, Association studies in Alzheimer's Disease, Systematic meta-analyses and risk loci, Genome-wide association studies (GWAS), Potential functional relevance, Next generation sequencing in Alzheimer's Disease